The Functional and Aesthetic Results of Fibrin Glue, Platelet-Rich Plasma (PRP), and Warm Blood as a Scaffold for Diced Cartilage in Saddle Nose Deformity: A Descriptive Study - Rabie, Amr Nabil; El samny, Talat Ali; Askoura, Anas Mohammad; Desouky, Mohamed Salah; Aty, Ahmed Mohamed Kamel Abdel (Facial Plastic Surgery, 2025)
Irregularities on the nasal dorsum post rhinoplasty remain a prevalent concern for both surgeons and patients. Various techniques using cartilage are used to hide the nasal dorsum, such as crushed cartilage, free diced cartilage, surgical-wrapped diced cartilage, or diced cartilage mixed with blood glue. Diced cartilage can address issues that arise with solid materials. However, it may lead to undesirable outcomes such as graft deformation and migration. It is challenging to uniformly implant the loosely linked cartilage pieces. To prevent issues, cartilage is mixed with other materials to serve as a stabilizing scaffold.This descriptive study will examine fibrin glue, platelet-rich plasma (PRP), and warm blood as stabilizing scaffolds for correcting saddle nose deformity.To compare functional and aesthetic results of the fibrin glue, PRP, and warm blood usage with diced cartilage for correction of saddle nose deformity in rhinoplasty as a descriptive study.This prospective interventional study was conducted on 30 patients with saddle nose undergoing rhinoplasty with dorsal nasal augmentation using three materials to collide the diced cartilage. All patients were divided into three groups: Study group 1 includes 10 patients who used fibrin glue. Study group 2 includes 10 patients who used PRP. Study group 3 includes 10 patients who used warm blood in Otorhinolaryngology Department, Faculty of Medicine, Ain Shams University hospitals from August 2021 till July 2023. The study was approved by an ethical committee before the start of the recruitment (FMASU M D 44/2021).Our study included 19 primary and 11 revision cases. The mean age of the patients was 31.10 years. Mean postoperative follow-up period was 12 months. There was a statistically significant improvement in rhinoplasty outcome evaluation score (ROE) and dorsal height postoperatively among the studied patients with p-value <0.001, with no statistical difference between the three different groups regarding postoperative resorption.One can augment the nasal dorsum significantly with diced cartilage combined with any of the three different materials, fibrin glue, PRP (PRP), or warm blood, guided by the availability of prerequisites of each material. As the warm blood can fit any patient with no required complex tools, it seems to be the best material to correct saddle nose and maintain the nasal dorsal height.
Keywords: fibrin glue; platelet-rich plasma; PRP; warm blood; saddle nose; dorsal irregularities; dorsal height; ROE